2013
DOI: 10.1103/physrevb.87.174522
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of a Cooper-pair box coupled to a two-level system via charge and critical current

Abstract: We report on the quadrupling of the transition spectrum of an Al/AlOx/Al Cooper-pair box (CPB) charge qubit in the 4.0 − 7.3 GHz frequency range. The qubit was coupled to a quasi-lumped element Al superconducting resonator and measured at a temperature of 25 mK. We obtained good matches between the observed spectrum and the spectra calculated from a model Hamiltonian containing two distinct low excitation energy two-level systems (TLS) coupled to the CPB. In our model, each TLS has a charge that tunnels betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Extensive prior work examining the charge offset stability of various materials showed that metallic SETs incorporating AlO x tunnel barriers demonstrate severe time instability-random, time-dependent phase fluctuations in the control curve [13][14][15][16][17][18] . These large, abrupt changes are attributed to two-level system (TLS) defects associated with amorphous AlO x , consistent with similar findings from TLS spectroscopy studies in the context of superconducting qubits [19][20][21] . In our prior work, we mitigated long-term, macroscopic resistance drift using plasma oxidized AlO x tunnel barrier devices 22 , a behavior thought to originate from the same bath of defects that causes significant charge offset drift 23,24 .…”
Section: Reduction Of Charge Offset Drift Using Plasma Oxidized Alumisupporting
confidence: 83%
“…Extensive prior work examining the charge offset stability of various materials showed that metallic SETs incorporating AlO x tunnel barriers demonstrate severe time instability-random, time-dependent phase fluctuations in the control curve [13][14][15][16][17][18] . These large, abrupt changes are attributed to two-level system (TLS) defects associated with amorphous AlO x , consistent with similar findings from TLS spectroscopy studies in the context of superconducting qubits [19][20][21] . In our prior work, we mitigated long-term, macroscopic resistance drift using plasma oxidized AlO x tunnel barrier devices 22 , a behavior thought to originate from the same bath of defects that causes significant charge offset drift 23,24 .…”
Section: Reduction Of Charge Offset Drift Using Plasma Oxidized Alumisupporting
confidence: 83%
“…One notable experiment which found direct indication that TLS modify the critical current of a Josephson junction was reported by Zaretskey et al (2013). Here, the spectrum of a Cooper-pair box was observed to be twinned, displaying multiple parabolas shifted both in frequency and offset in gate charge.…”
Section: Tls Interactionsmentioning
confidence: 72%
“…As shown in equations (27) and (28), the parameters ν n and t n , n +1 contain both the Josephson coupling E J 0 and the flux . Therefore, the local perturbations and can be contributed by both the critical-current 37 and flux fluctuations.…”
Section: Resultsmentioning
confidence: 99%